Tower of Jewels (Pacific Novelty Co.)
On verso: The Tower of Jewels is the dominating architectural feature of the Exposition. It is 433 feet high and covers more than an acre of ground. Through the base is a vaulted entrance 60 feet wide and 110 feet high. The tower is adorned with more than 90,000 specially prepared "Novagems" or "glass jewels," and, particularly at night, when the searchlights and other concealed lights are flashed on the tower, the effect is truly marvelous. the design is by Carrere and Hastings, New York.